Kepastian Hukum Penetapan Perwalian Terhadap Penyandang Disabilitas Dewasa Yang Telah Ditetapkan Di Bawah Perwalian - R. Amalia Polopadang; Rielly Lontoh; H. M. Slamet Turhamun (Journal of Innovation Research and Knowledge, 2026)
Persons with disabilities are entitled to equal recognition before the law and to legal protection and legal certainty. In practice, however, some adults with disabilities have been placed under legal guardianship through court orders, resulting in legal issues concerning the validity and implications of such determinations. This study addresses two research questions: what are the legal consequences of placing adults with disabilities under guardianship in light of Legislation governing persons with disabilities, and how does legal certainty apply to court orders placing adults with disabilities under legal guardianship. This study is based on Soeroso's theory of legal consequences and Gustav Radbruch's theory of legal certainty. This study employed a normative juridical research method based on library research and secondary data obtained from primary, secondary, and tertiary legal sources. It adopted statutory, case, and analytical approaches. Legal materials were collected through the identification and inventory of positive legal regulations, books, journal articles, and other relevant legal sources. Data analysis used grammatical, systematic, and analogical methods of legal interpretation. The findings of the study indicate that the legal consequence of imposing guardianship on adults with disabilities causes juridical issues and potential legal disputes, as the appropriate legal mechanism should be conservatorship, not guardianship. The judges' error in applying guardianship as the legal instrument for adults with disabilities, contrary to the applicable statutory provisions, results in legal uncertainty. Therefore, judges should carefully identify whether a petition or claim concerning guardianship has been appropriately filed before proceeding to the substantive examination of the case. Moreover, the Supreme Court should develop technical guidelines for adjudicating cases involving adults with disabilities, particularly concerning guardianship and conservatorship